LEARNING THROUGH WATCHING FILMS - Dr.Rudy MA; jamaluddin Nasution; Kartina Rahmadhani Rambe (English Language Teaching Prima Journal (ELT), 2019)
As one of the most important aspects in people’s life, education should be treated and improved well. It is so essential because education gives opportunity to have a better life. Therefore, people should think of any better ways to improve the quality of education. One of the ways is through popular culture. As a growing-trend culture, popular culture has been widely known, especially by young people. From the library research conducted, some relevant references have been gathered and the data analysis has shown that it is very acceptable to use films, a part of popular culture to teach. This teaching technique can be used to teach morality and language skills at the same time. Therefore, education institution should be able to accommodate this system in order to succeed in educating.